The myths of origin in the Community of Andamarca (Ayacucho-Peru) - Ossio, Juan M. (1977)
During the last 20 or 30 years, a growing interest can be observed, both by national and foreign researchers, for the Andean myths, especially those that refer to Incarrí, to the historical evolution, to the apus or wamanis or other divinities already known. Andean or Christian origin. This interest has given rise, in turn, to the popularization of scholars such as Mircea Eliada and Lévi-Strauss, whose works have been translated almost entirely into Spanish, in our academic environment. As a consequence, little by little we find ourselves better equipped to collect and interpret these oral testimonies of our indigenous populations and to be able to fully reassess their creative potential.